2020
DOI: 10.1109/access.2020.3040737
|View full text |Cite
|
Sign up to set email alerts
|

Image Colorization Using the Global Scene-Context Style and Pixel-Wise Semantic Segmentation

Abstract: In this paper, we present an encoder-decoder architecture that exploits global and local semantics for the automatic image colorization problem. For the global semantics, the low-level encoding features are fine-tuned by the scene-context classification to integrate the global image style. Moreover, the architecture deals with the uncertainty and relations among the scene styles based on the label smoothing and pre-trained weights from Places365. For local semantics, three branches learn the mutual benefits at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…They use a GAN encoder to first find matching features that are similar to exemplars, and after that modulate these features into the colorization process. Using both global and local priors, Nguyen-Quynh et al [38] suggested an encoder-decoder image colorization model. By using picture detection, they hone low-level encoding features for the global priors.…”
Section: Learning-based Colorizationmentioning
confidence: 99%
“…They use a GAN encoder to first find matching features that are similar to exemplars, and after that modulate these features into the colorization process. Using both global and local priors, Nguyen-Quynh et al [38] suggested an encoder-decoder image colorization model. By using picture detection, they hone low-level encoding features for the global priors.…”
Section: Learning-based Colorizationmentioning
confidence: 99%
“…They used a GAN encoder to first find matching features that are similar to exemplars, and after that modulate these features into the colorization process. Nguyen-Quynh et al [37] suggested an encoder-decoder image colorization model by exploiting both global and local priors. Bahng et.…”
Section: B Related Workmentioning
confidence: 99%
“…Another study proposed a label smoothing approach to improve the model uncertainty calibration for scene segmentation [33]. In the context of image colorization, one study used label smoothing to achieve more accurate scene segmentation [34]. However, none of these studies have properly addressed the spatially-varying nature of boundary uncertainty in semantic segmentation.…”
Section: B Segmentation With Noisy Labelsmentioning
confidence: 99%